Specific engagement of the CD94/NKG2-A killer inhibitory receptor by the HLA-E class Ib molecule induces SHP-1 phosphatase recruitment to tyrosine-phosphorylated NKG2-A: evidence for receptor function in heterologous transfectants - Marta Carretero; Gabriella Palmieri; Manuel Llano; Valentino Tullio; Angela Santoni; Daniel E. Geraghty; Miguel López‐Botet (1998)
It has been recently demonstrated that the CD94/NKG2-A killer inhibitory receptor (KIR) specifically recognizes the HLA-E class Ib molecule. Moreover, the apparent CD94-mediated specific recognition of different HLA class Ia allotypes, transfected into the HLA-defective cell line 721.221, indeed depends on their selective ability to concomitantly stabilize the surface expression of endogenous HLA-E molecules, which confer protection against CD94/NKG2-A+ effector cells. In the present study, we show that a selective engagement of the CD94/NKG2-A inhibitory receptor with a specific monoclonal antibody (mAb) (Z199) was sufficient to induce tyrosine phosphorylation of the NKG2-A subunit and SHP-1 recruitment. These early biochemical events, commonly related to negative signaling pathways, were also detected upon the specific interaction of NK cells with an HLA-E+ 721.221 transfectant (.221-AEH), and were prevented by pre-incubation of .221-AEH with an anti-HLA class I mAb. Furthermore, mAb cross-linking of the CD94/NKG2-A receptor, segregated from other NK-associated molecules by transfection into a rat basophilic leukemia cell line (RBL-2H3), promoted tyrosine phosphorylation of NKG2-A and co-precipitation of SHP-1, together with an inhibition of secretory events triggered via FcϵRI. Remarkably, interaction of CD94/NKG2-A+ RBL cells with the HLA-E+ .221-AEH transfectant specifically induced a detectable association of SHP-1 with NKG2-A, constituting a more formal evidence for the receptor-HLA class I interaction.